2002
DOI: 10.1176/appi.ajp.159.7.1127
|View full text |Cite
|
Sign up to set email alerts
|

Are Depressive Symptoms a Risk Factor for Mortality in Elderly Japanese American Men?: The Honolulu-Asia Aging Study

Abstract: Depressive symptoms are a risk factor for mortality in elderly people, particularly in physically healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 33 publications
6
62
0
2
Order By: Relevance
“…In line, the mortality risks of depressed participants remained increased in participants who were independent in activities of daily living, in participants with good cognitive function, and in those without chronic diseases. These results demonstrate that the excess of mortality is not only caused by co-morbidity and frailty, as was already mentioned by other authors (Wulsin, 2000;Takeshita et al, 2002). Furthermore, antidepressive pharmacotherapy was almost nonexistent in our population (Stek et al, 2004a), which makes it unlikely that treatment effects of depression increase mortality.…”
Section: Discussionsupporting
confidence: 84%
“…In line, the mortality risks of depressed participants remained increased in participants who were independent in activities of daily living, in participants with good cognitive function, and in those without chronic diseases. These results demonstrate that the excess of mortality is not only caused by co-morbidity and frailty, as was already mentioned by other authors (Wulsin, 2000;Takeshita et al, 2002). Furthermore, antidepressive pharmacotherapy was almost nonexistent in our population (Stek et al, 2004a), which makes it unlikely that treatment effects of depression increase mortality.…”
Section: Discussionsupporting
confidence: 84%
“…The summed score of the 11-question version CES-D ranged from 0-33 and the present study defined conditions with a summed score >9 as depressive symptoms (29). Several validation studies have shown that CES-D has a reasonable psychometric property in South Korea and other East-Asian countries (30)(31)(32)(33) .…”
Section: Outcome Variables and Covariatesmentioning
confidence: 74%
“…Several cohort studies have reported similar relative risk values of 1.02-3.36 (15)(16)(17). It remains unclear how depressive symptoms affect coronary heart disease and other complications, although several explanations have been put forward.…”
Section: Discussionmentioning
confidence: 99%